From Here to Eternity: Encountering the Divine in Martin Buber's I and Thou - Faught, Stephen A. (My University, 2004)
This thesis is an analysis of Martin Buber's famous work I and Thou. The primary aim of the thesis is to interpret or translate Buber's unique, impressionistic account of human existence into a coherent and revealing argument, one that is philosophically engaging and accessible to the common or everyday reader. In addition to providing a clear outline of Buber's work, this thesis also contains a short critique of Buber basic argument, i.e., his distinction between the two spheres or modes of our being, the I-It or active mode and the I-You or passive mode. In short, it argues that what results from Buber's dualistic understanding is division or separation between ourselves and the world, between an individual human being and the beings it engages, and not the genuine or authentic unity that Buber believes his position can inspire.
Keywords: Divine; Eternity; Philosophy; Religion; Philosophy; Philosophy